Preventive Effects of Ipratropium and Salbutamol Against Insulin Induced Tracheal Smooth Muscle Contraction in Guinea Pig Model: Ipratropium and Salbutamol inhibit Tracheal Contractions - Mahjabeen Sharif; Bushra Tayyaba Khan; Mubashir Sharif; Afsheen Sharif (Iranian Journal of Pharmaceutical Sciences, 2014)
https://doi.org/10.22034/IJPS.2014.15247 Inhalational insulin was withdrawn from the market due to its potential to produce airway hyper-reactivity and bronchoconstriction. So, the present study was designed to explore the acute effects of insulin on airway reactivity of guinea pigs and protective effects of salbutamol and ipratropium against insulin induced airway hyper-responsiveness on isolated tracheal smooth muscle of guinea pig. The tracheal muscle contractions were recorded with transducer on four channel oscillograph. The mean ± SEM of maximum amplitude of contraction with increasing concentrations of insulin (10-7- 10-3 M), insulin pretreated with fixed concentration of salbutamol (10-7 M) and ipratropium (10-6 M) were 35 ± 1.13 mm, 14.55 ± 0.62 mm, and 27.8 ± 1.27 mm respectively. Salbutamol inhibited the contractile response of insulin greater than ipratropium on isolated tracheal muscle of guinea pig. So, we suggest that pretreatment of inhaled insulin with salbutamol may be preferred over ipratropium in amelioration of its potential respiratory adverse effects such as bronchoconstriction.